2024
DOI: 10.1007/s00259-024-06717-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preclinical evaluation of novel 18F-vancomycin-based tracers for the detection of bacterial infections using positron emission tomography

G. B. Spoelstra,
S. N. Blok,
L. Reali Nazario
et al.

Abstract: Introduction Bacterial infections are a major problem in medicine, and the rapid and accurate detection of such infections is essential for optimal patient outcome. Bacterial infections can be diagnosed by nuclear imaging, but most currently available modalities are unable to discriminate infection from sterile inflammation. Bacteria-targeted positron emission tomography (PET) tracers have the potential to overcome this hurdle. In the present study, we compared three 18F-labelled PET tracers base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The authors concluded that [ 18 F]pretomanid-PET is a promising agent for the noninvasive pretomanid concentration measurement of various tissues. (Spoelstra et al 2024) the highest accumulation in the spleen and high signals were also detected in the blood pool, with some accumulation in the kidneys and bladder.…”
Section: [ 18 F]pretomanidmentioning
confidence: 95%
See 3 more Smart Citations
“…The authors concluded that [ 18 F]pretomanid-PET is a promising agent for the noninvasive pretomanid concentration measurement of various tissues. (Spoelstra et al 2024) the highest accumulation in the spleen and high signals were also detected in the blood pool, with some accumulation in the kidneys and bladder.…”
Section: [ 18 F]pretomanidmentioning
confidence: 95%
“…The major pharmacological action of vancomycin is against Gram-positive bacteria. Spoelstra et al ( 2024 ) utilised these characteristics to synthesise and investigate three vancomycin-based tracers labelled with 18 F, i.e. [ 18 F]FB-vancomycin, [ 18 F]BODIPY-FL-vancomycin and [ 18 F]PQ-VE1-vancomycin (see Fig.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations